# Duhamel's integral

In theory of vibrations, Duhamel's integral is a way of calculating the response of linear systems and structures to arbitrary time-varying external perturbation.

## Introduction

### Background

The response of a linear, viscously damped single-degree of freedom (SDOF) system to a time-varying mechanical excitation p(t) is given by the following second-order ordinary differential equation

${\displaystyle m{\frac {d^{2}x(t)}{dt^{2}}}+c{\frac {dx(t)}{dt}}+kx(t)=p(t)}$

where m is the (equivalent) mass, x stands for the amplitude of vibration, t for time, c for the viscous damping coefficient, and k for the stiffness of the system or structure.

If a system initially rests at its equilibrium position, from where it is acted upon by a unit-impulse at the instance t=0, i.e., p(t) in the equation above is a Dirac delta function δ(t), ${\displaystyle x(0)=\left.{\frac {dx}{dt}}\right|_{t=0}=0}$, then by solving the differential equation one can get a fundamental solution (known as a unit-impulse response function)

${\displaystyle h(t)={\begin{cases}{\frac {1}{m\omega _{d}}}e^{-\varsigma \omega _{n}t}\sin \omega _{d}t,&t>0\\0,&t<0\end{cases}}}$

where ${\displaystyle \varsigma ={\frac {c}{2{\sqrt {km}}}}}$ is called the damping ratio of the system, ${\displaystyle \omega _{n}={\sqrt {\frac {k}{m}}}}$ is the natural angular frequency of the undamped system (when c=0) and ${\displaystyle \omega _{d}=\omega _{n}{\sqrt {1-\varsigma ^{2}}}}$ is the circular frequency when damping effect is taken into account (when ${\displaystyle c\neq 0}$). If the impulse happens at t=τ instead of t=0, i.e. ${\displaystyle p(t)=\delta (t-\tau )}$, the impulse response is

${\displaystyle h(t-\tau )={\frac {1}{m\omega _{d}}}e^{-\varsigma \omega _{n}(t-\tau )}\sin[\omega _{d}(t-\tau )]}$${\displaystyle t\geq \tau }$

### Conclusion

Regarding the arbitrarily varying excitation p(t) as a superposition of a series of impulses:

${\displaystyle p(t)\approx \sum _{\tau

then it is known from the linearity of system that the overall response can also be broken down into the superposition of a series of impulse-responses:

${\displaystyle x(t)\approx \sum _{\tau

Letting ${\displaystyle \Delta \tau \to 0}$, and replacing the summation by integration, the above equation is strictly valid

${\displaystyle x(t)=\int _{0}^{t}{p(\tau )h(t-\tau )d\tau }}$

Substituting the expression of h(t-τ) into the above equation leads to the general expression of Duhamel's integral

${\displaystyle x(t)={\frac {1}{m\omega _{d}}}\int _{0}^{t}{p(\tau )e^{-\varsigma \omega _{n}(t-\tau )}\sin[\omega _{d}(t-\tau )]d\tau }}$

### Mathematical Proof

The above SDOF dynamic equilibrium equation in the case p(t)=0 is the homogeneous equation:

${\displaystyle {\frac {d^{2}x(t)}{dt^{2}}}+{\bar {c}}{\frac {dx(t)}{dt}}+{\bar {k}}x(t)=0}$, where ${\displaystyle {\bar {c}}={\frac {c}{m}},{\bar {k}}={\frac {k}{m}}}$

The solution of this equation is:

${\displaystyle x_{h}(t)=C_{1}\cdot e^{-{\frac {1}{2}}({\bar {c}}+{\sqrt {{\bar {c}}^{2}-4\cdot {\bar {k}}}})t}+C_{2}\cdot e^{{\frac {1}{2}}(-{\bar {c}}+{\sqrt {{\bar {c}}^{2}-4\cdot {\bar {k}}}})t}}$

The substitution: ${\displaystyle A={\frac {1}{2}}({\bar {c}}-{\sqrt {{\bar {c}}^{2}-4{\bar {k}}}}),\;B={\frac {1}{2}}({\bar {c}}+{\sqrt {{\bar {c}}^{2}-4{\bar {k}}}}),\;P={\sqrt {{\bar {c}}^{2}-4{\bar {k}}}},\;P=B-A}$ leads to:

${\displaystyle x_{h}(t)=C_{1}e^{-B\cdot t}\;+\;C_{2}e^{-A\cdot t}}$

One partial solution of the non-homogeneous equation: ${\displaystyle {\frac {d^{2}x(t)}{dt^{2}}}+{\bar {c}}{\frac {dx(t)}{dt}}+{\bar {k}}x(t)={\bar {p(t)}}}$, where ${\displaystyle {\bar {p(t)}}={\frac {p(t)}{m}}}$, could be obtained by the Lagrangian method for deriving partial solution of non-homogeneous ordinary differential equations.

This solution has the form:

${\displaystyle x_{p}(t)={\frac {\int {{\bar {p(t)}}\cdot e^{At}dt}\cdot e^{-At}-\int {{\bar {p(t)}}\cdot e^{Bt}dt}\cdot e^{-Bt}}{P}}}$

Now substituting:${\displaystyle \int {{\bar {p(t)}}\cdot e^{At}dt}|_{t=z}=Q_{z},\int {{\bar {p(t)}}\cdot e^{Bt}dt}|_{t=z}=R_{z}}$,where ${\displaystyle \int {x(t)dt}|_{t=z}}$ is the primitive of x(t) computed at t=z, in the case z=t this integral is the primitive itself, yields:

${\displaystyle x_{p}(t)={\frac {Q_{t}\cdot e^{-At}-R_{t}\cdot e^{-Bt}}{P}}}$

Finally the general solution of the above non-homogeneous equation is represented as:

${\displaystyle x(t)=x_{h}(t)+x_{p}(t)=C_{1}\cdot e^{-Bt}+C_{2}\cdot e^{-At}+{\frac {Q_{t}\cdot e^{-At}-R_{t}\cdot e^{-Bt}}{P}}}$

with time derivative:

${\displaystyle {\frac {dx}{dt}}=-Ae^{-At}\cdot C_{2}-Be^{-Bt}\cdot C_{1}+{\frac {1}{P}}[{\dot {Q_{t}}}\cdot e^{-At}-AQ_{t}\cdot e^{-At}-{\dot {R_{t}}}\cdot e^{-Bt}+BR_{t}\cdot e^{-Bt}]}$, where ${\displaystyle {\dot {Q_{t}}}=p(t)\cdot e^{At},{\dot {R_{t}}}=p(t)\cdot e^{Bt}}$

In order to find the unknown constants ${\displaystyle C_{1},C_{2}}$, zero initial conditions will be applied:

${\displaystyle x(t)|_{t=0}=0:C_{1}+C_{2}+{\frac {Q_{0}\cdot 1-R_{0}\cdot 1}{P}}=0}$${\displaystyle C_{1}+C_{2}={\frac {R_{0}-Q_{0}}{P}}}$
${\displaystyle \left.{\frac {dx}{dt}}\right|_{t=0}=0:-A\cdot C_{2}-B\cdot C_{1}+{\frac {1}{P}}\cdot [-A\cdot Q_{0}+B\cdot R_{0}]=0}$${\displaystyle A\cdot C_{2}+B\cdot C_{1}={\frac {1}{P}}\cdot [B\cdot R_{0}-A\cdot Q_{0}]}$

Now combining both initial conditions together, the next system of equations is observed:

{\displaystyle \left.{\begin{alignedat}{5}C_{1}&&\;+&&\;C_{2}&&\;=&&\;{\frac {R_{0}-Q_{0}}{P}}&\\B\cdot C_{1}&&\;+&&\;A\cdot C_{2}&&\;=&&\;{\frac {1}{P}}\cdot [B\cdot R_{0}-A\cdot Q_{0}]\end{alignedat}}\right|{\begin{alignedat}{5}C_{1}&&\;=&&\;{\frac {R_{0}}{P}}&\\C_{2}&&\;=&&\;-{\frac {Q_{0}}{P}}\end{alignedat}}}

The back substitution of the constants ${\displaystyle C_{1}}$ and ${\displaystyle C_{2}}$ into the above expression for x(t) yields:

${\displaystyle x(t)={\frac {Q_{t}-Q_{0}}{P}}\cdot e^{-A\cdot t}-{\frac {R_{t}-R_{0}}{P}}\cdot e^{-B\cdot t}}$

Replacing ${\displaystyle Q_{t}-Q_{0}}$ and ${\displaystyle R_{t}-R_{0}}$ (the difference between the primitives at t=t and t=0) with definite integrals (by another variable τ) will reveal the general solution with zero initial conditions, namely:

${\displaystyle x(t)={\frac {1}{P}}\cdot [\int _{0}^{t}{{\bar {p(\tau )}}\cdot e^{A\tau }d\tau }\cdot e^{-At}-\int _{0}^{t}{{\bar {p(\tau )}}\cdot e^{B\tau }d\tau }\cdot e^{-Bt}]}$

Finally substituting ${\displaystyle c=2\xi \omega m,\;k=\omega ^{2}m}$, accordingly ${\displaystyle {\bar {c}}=2\xi \omega ,{\bar {k}}=\omega ^{2}}$, where ξ<1 yields:

${\displaystyle P=2\omega _{D}i,\;A=\xi \omega -\omega _{D}i,\;B=\xi \omega +\omega _{D}i}$, where ${\displaystyle \omega _{D}=\omega \cdot {\sqrt {1-\xi ^{2}}}}$ and i is the imaginary unit.

Substituting this expressions into the above general solution with zero initial conditions and using the Euler's exponential formula will lead to canceling out the imaginary terms and reveals the Duhamel's solution:

${\displaystyle x(t)={\frac {1}{\omega _{D}}}\int _{0}^{t}{{\bar {p(\tau )}}e^{-\xi \omega (t-\tau )}sin(\omega _{D}(t-\tau ))d\tau }}$